Cement-based phase change aggregate and preparation method thereof
By adsorbing the inorganic and organic phase change materials and coating the epoxy emulsion to form the phase change aggregate for cement-based materials, the volume change, heat storage attenuation and seepage of the phase change materials in the cement-based materials in the prior art is solved. The leakage problem has achieved efficient phase change energy storage and anti-leakage effect under multi-temperature conditions, and improved the heat storage performance of cement-based materials.
Patent Information
- Application Number
- CN202411300086.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-17
AI Technical Summary
The existing method of implanting phase change materials into cement-based materials has problems such as before and after volume changes, attenuation of heat storage performance, leakage and low adsorption rate, resulting in defects in engineering applications.
The ceramic particles are successively adsorbed inorganic phase change materials and organic phase change materials, and coated with epoxy emulsion on the surface of the ceramic particles to cure them to form cement-based phase change aggregates, and use phase change combinations of inorganic and organic energy storage to avoid water absorption. Failure of phase change function and leakage.
The latent heat of phase change is increased under multiple temperature conditions, effectively preventing leakage of phase change materials, overcoming the defects of the prior art, and improving the heat storage and energy saving effect of cement-based materials.
Smart Images

Figure CN119320251A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of phase change materials, and in particular to a cement-based phase change aggregate and a preparation method thereof. Background Art
[0002] The research on phase change materials focuses on the fields of energy storage and building energy conservation. In the early stage of research, gypsum boards, thermal insulation materials and finishing materials were mostly used as the matrix. In recent years, the application of phase change materials in cement-based materials has attracted widespread attention. The reason is that cement-based materials are the most used building materials and have a larger heat capacity than wall materials such as gypsum. Using cement-based materials as the matrix of phase change materials will achieve better heat storage and energy saving effects.
[0003] At present, the main methods for implanting phase change materials into cement-based materials are direct addition, impregnation and adsorption, shaping and encapsulation, and capsule packaging. Each of these four methods has its own defects. For example, the direct addition method has the problem of volume change before and after, the impregnation and adsorption method has the problem of heat storage performance attenuation and phase change material leakage, the shaping and encapsulation method has the problem of low adsorption rate, and the capsule packaging method has the problem of low heat storage efficiency. Therefore, it is urgent to propose a new method for implanting phase change materials into cement-based materials to improve the defects of the existing technology. Summary of the invention
[0004] The object of the present invention is to provide a cement-based phase change aggregate and a preparation method thereof to improve the above-mentioned problems. In order to achieve the above-mentioned object, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing a cement-based phase change aggregate, comprising:
[0006] Immersing the ceramsite in a liquid inorganic phase change material for adsorption to obtain ceramsite adsorbed with the inorganic phase change material;
[0007] Immersing the ceramsite adsorbed with the inorganic phase change material into a liquid organic phase change material for adsorption to obtain phase change ceramsite;
[0008] Epoxy emulsion is coated on the surface of the phase-change ceramsite, and after the epoxy emulsion is cured, a cement-based phase-change aggregate is obtained. The components of the epoxy emulsion include epoxy resin, diluent and curing agent.
[0009] Optionally, the inorganic phase change material includes CaCl 2 6H 2 O、Na 2 HPO 4 12H 2 O、Na 2 S 2 O 3 ·5H 2 O and Na 2 SO4 10H 2 At least one of O.
[0010] Optionally, the mechanical phase change material includes C 25 H 32 , C 18 H 38 , C 22 H 44 O 2 , C 12 H 26 O.C 16 H 32 O 2 , C 10 H 20 O 2 and C 12 H 24 O 2 At least one of .
[0011] Optionally, the particle size of the ceramsite is 5mm-10mm.
[0012] Optionally, the porosity of the ceramsite is 50-80%.
[0013] Optionally, in the epoxy emulsion, the mass ratio of the epoxy resin, the diluent and the curing agent is 1:(0.1-0.3):(0.1-0.5).
[0014] Optionally, immersing the ceramsite in a liquid inorganic phase change material for adsorption comprises:
[0015] heating the inorganic phase change material to above its phase change temperature;
[0016] The ceramsite is completely immersed in the inorganic phase change material, and the surface of the ceramsite in contact with the bottom of the container is adjusted every 2.5-4 hours until all six surfaces of the ceramsite are in contact with the bottom of the container once.
[0017] Optionally, the diluent includes at least one of acetone, toluene, xylene, styrene, ethyl acetate and butyl acetate.
[0018] Optionally, the curing agent is an amine curing agent.
[0019] On the other hand, the present application also provides a cement-based phase change aggregate, which is prepared by the above-mentioned preparation method.
[0020] The beneficial effects of the present invention are:
[0021] The ceramsite of the present invention successively absorbs inorganic phase change material and organic phase change material. The inorganic and organic materials are combined to play the role of phase change energy storage under multiple temperature conditions, and the latent heat of phase change is significantly improved. At the same time, the ceramsite is encapsulated twice by using organic phase change material and epoxy resin successively, which can effectively prevent the inorganic phase change material from failing in phase change heat storage function due to water absorption during use, avoid the leakage problem of the phase change material, and overcome the defects of the inorganic phase change material in engineering applications.
[0022] Other features and advantages of the present invention will be set forth in the following description, and in part will become apparent from the description, or may be understood by practicing embodiments of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 The phase change material permeability diagram of the aggregate prepared in Comparative Example 1 of the present application;
[0025] Figure 2 The phase change material permeability diagram of the aggregate prepared in Example 1 of the present application;
[0026] Figure 3 The adiabatic temperature rise curves of the reference group and the doped phase-change ceramsite group in the embodiment of the present application;
[0027] Figure 4 Schematic diagram of the curing method of concrete in the embodiment of the present application;
[0028] Figure 5 This is a graph showing the relationship between the compressive strength of concrete and the curing time for the baseline group and the doped phase-change ceramsite group in the embodiments of the present application. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. The following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0031] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0032] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0033] Phase Change Materials (PCMs) are a type of latent heat storage material with the advantages of large heat storage per unit volume, approximately isothermal heat storage and release process, and stable chemical properties. The relationship between the temperature and energy changes of phase change materials during phase change is as follows: when the phase change material is in the solid stage or completely turns into a liquid stage, energy storage or release is achieved by increasing or decreasing the temperature, which is the sensible heat storage stage; during the phase change process, the temperature remains constant, and energy storage or release is achieved through phase change, which is the latent heat storage stage. The research on phase change materials focuses on the fields of energy storage and building energy conservation. In the early stages of research, gypsum boards, insulation materials, and finishing materials were used as the matrix. In recent years, the application of phase change materials in cement-based materials has attracted widespread attention. The reason is that cement-based materials are the most used building materials and have a larger heat capacity than wall materials such as gypsum. Using cement-based materials as the matrix of phase change materials will achieve better heat storage and energy saving effects.
[0034] There are four main ways to implant phase change materials into cement-based materials: direct addition, impregnation and adsorption, shaping and encapsulation, and encapsulation. The direct addition method is to directly add the phase change material as a component during the mixing process of cement-based materials. This method is simple to operate and low in cost, but it will face problems such as low strength of the phase change material itself, volume change before and after phase change, attenuation of heat storage performance, corrosion to the matrix, and poor durability; the impregnation and adsorption method is to use the capillary action of the pores of cement-based materials to directly adsorb liquid phase change materials. This method is relatively simple, but time-consuming, and the impregnated and adsorbed phase change material is unevenly distributed in the matrix, and the surface content is higher than that in the interior. This method faces the problem of leakage of the phase change material. In addition, temperature and concrete specimen age will also indirectly affect the efficiency of impregnation and adsorption. Since there are many factors that affect the amount of impregnation adsorption, this method has limitations in practical applications; the shaping and encapsulation method is a method of encapsulating the phase change material to avoid leakage of the phase change material during the solid-liquid phase change, and the phase change material enters the porous material through physical adsorption. This method can effectively prevent leakage of phase change materials, but there are problems such as low adsorption rate of phase change materials and high preparation cost. The encapsulation method is to encapsulate the phase change materials in containers such as tubes, shells, bags, etc. to avoid leakage problems and isolate the phase change materials from the matrix. The encapsulation container should be made of materials with high thermal conductivity and good compatibility. This encapsulation method is simple to operate and has high feasibility, but the phase change material is easy to solidify at the boundary, and the low thermal conductivity can easily lead to low utilization rate and heat storage efficiency of the phase change material. In addition, drilling holes in the later decoration can easily lead to the destruction of large-volume capsules.
[0035] In order to solve the problems existing in the prior art, the present application provides a method for preparing a cement-based phase change aggregate, comprising:
[0036] The ceramsite is immersed in a liquid inorganic phase change material for adsorption, so as to obtain the ceramsite adsorbed with the inorganic phase change material;
[0037] The ceramsite adsorbed with the inorganic phase change material is immersed in a liquid organic phase change material for adsorption to obtain a phase change ceramsite; the phase change temperature of the inorganic phase change material is lower than the phase change temperature of the organic phase change material;
[0038] Epoxy emulsion is coated on the surface of the phase-change ceramsite, and after the epoxy emulsion is cured, a cement-based phase-change aggregate is obtained. The components of the epoxy emulsion include epoxy resin, diluent and curing agent.
[0039] As an optional implementation, the ceramsite has a porosity of 50-80%, a water absorption rate of ≥40%, an impurity content of ≤5%, and must not be mixed with debris or clay lumps, has a good particle gradation, and a round or oval surface.
[0040] As an optional embodiment, the inorganic phase change material includes CaCl 26H 2 O、Na 2 HPO 4 12H 2 O、Na 2 S 2 O 3 ·5H 2 O and Na 2 SO 4 10H 2 At least one of O.
[0041] As an optional embodiment, the mechanical phase change material includes C 25 H 32 , C 18 H 38 , C 22 H 44 O 2 , C 12 H 26 O.C 16 H 32 O 2 , C 10 H 20 O 2 and C 12 H 24 O 2 At least one of .
[0042] As an optional embodiment, the particle size of the ceramsite is 5 mm to 10 mm. The ceramsite within this particle size range can replace aggregate and be added to concrete.
[0043] As an optional embodiment, in the epoxy emulsion, the mass ratio of the epoxy resin, the diluent and the curing agent is 1: (0.1-0.3): (0.1-0.5). The diluent is used to enhance the fluidity of the emulsion so that it can be evenly wrapped on the surface of the ceramsite. As the diluent evaporates, the resin slowly solidifies, thus forming a hardened epoxy resin layer on the surface of the porous ceramsite, which plays a good secondary packaging role for the porous ceramsite.
[0044] As an optional embodiment, the ceramsite is immersed in a liquid inorganic phase change material for adsorption, comprising:
[0045] The inorganic phase change material is heated to above its phase change temperature; preferably heated to 10-20°C above the phase change temperature to ensure that it is completely liquid;
[0046] The ceramsite is completely immersed in the inorganic phase change material. Since the adsorption effect will be very poor when the bottom surface of the ceramsite contacts the container, the surface of the ceramsite in contact with the bottom of the container needs to be adjusted every 2.5-4 hours, that is, the ceramsite is turned over until all six surfaces of the ceramsite contact the bottom of the container once, and uniform adsorption is completed. The adsorption operation of the organic phase change material is the same.
[0047] As an optional implementation, the diluent is at least one of acetone, toluene, xylene, styrene, ethyl acetate and butyl acetate.
[0048] As an optional embodiment, the curing agent is an amine curing agent. It should be noted that, due to the presence of phase change materials, it is preferred to use a curing agent that cures at room temperature, such as aliphatic amines, aromatic amines, alicyclic amines, polyether amines, aromatic amines, and polyamides.
[0049] Based on the same inventive concept, the present application also provides a cement-based phase change aggregate, which is prepared by the above-mentioned preparation method.
[0050] The present application firstly allows ceramsite to absorb inorganic phase change material, then uses organic phase change material to encapsulate ceramsite once, and finally uses epoxy resin to encapsulate it twice, forming a hardened epoxy resin layer on the surface of porous ceramsite, which plays a good secondary encapsulation role for porous ceramsite. The prepared phase change material can replace part of the aggregate and be directly incorporated into cement-based materials. Moreover, ceramsite has good adsorption and thermal conductivity for phase change material, which effectively improves the heat storage and energy-saving effect of cement-based materials.
[0051] The following describes the embodiments of the present invention through specific examples.
[0052] Example 1
[0053] A method for preparing a cement-based phase change aggregate, comprising:
[0054] The porous ceramsite with a particle size of 5mm-10mm and good gradation is used as the porous aggregate for preparing the phase change aggregate. Its porosity is 60%, water absorption rate is 45%, impurity content is 1.6%, and there is no debris or clay block. The appearance is oval; the inorganic phase change material selected is CaCl 2 6H 2 O, its phase change temperature is 29.7℃; the organic phase change material selected is C 25 H 32 , and its phase transition temperature is 35℃.
[0055] CaCl 2 6H 2 O and C 25 H 32Put it in a temperature regulating box at 45℃ or 50℃ and keep it warm for 2.5 hours to turn it into a liquid state.
[0056] Then put 500g of porous ceramsite into CaCl 2 6H 2 O in a temperature regulating box for adsorption, adjusting the ceramsite every 3 hours until all 6 sides are adsorbed, and obtaining ceramsite adsorbed with inorganic phase change material;
[0057] Place the ceramsite adsorbed with inorganic phase change material into C 25 H 32 The ceramsite was placed in a temperature regulating box and the ceramsite was adjusted every 3 hours until all 6 sides were adsorbed. After the adsorption was completed, the ceramsite was placed in a temperature regulating box at 15°C for 30 minutes to make the adsorbed organic phase change material change into a solid state to obtain phase change ceramsite.
[0058] Finally, epoxy resin, acetone and curing agent were mixed and stirred in a mass ratio of 1:0.15:0.25 to obtain epoxy emulsion. Phase change ceramsite was placed in the epoxy emulsion and stirred. After 10 seconds, it was scooped out with a colander and spread evenly until the epoxy resin hardened. An epoxy resin encapsulation layer was formed on the surface of the porous ceramsite, and the cement-based phase change aggregate was prepared.
[0059] Example 2
[0060] A method for preparing a cement-based phase change aggregate, comprising:
[0061] The porous ceramsite with a particle size of 5mm-10mm and good gradation is used as the porous aggregate for preparing phase change aggregate. Its porosity is 50%, water absorption rate is 42%, impurity content is 2.4%, and there is no debris or clay block. The appearance is oval; the inorganic phase change material selected is Na 2 HPO 4 12H 2 O, its phase change temperature is 35.4℃; the organic phase change material selected is C 22 H 44 O 2 , and its phase transition temperature is 80℃.
[0062] Na 2 SO 4 10H 2 O and C 12 H 26 O was placed in a temperature regulating box at 50°C and 90°C for 2 hours to turn it into a liquid state.
[0063] Then put 500g of porous ceramsite into Na 2 SO 4 10H 2O in a temperature regulating box for adsorption, adjusting the ceramsite once, until all 6 sides are adsorbed, to obtain ceramsite adsorbed with inorganic phase change material;
[0064] Place the ceramsite adsorbed with inorganic phase change material into C 22 H 44 O 2 The ceramsite was placed in a temperature regulating box and the ceramsite was adjusted every 4 hours until all 6 sides were adsorbed. After the adsorption was completed, the ceramsite was placed in a temperature regulating box at 15°C for 30 minutes to make the adsorbed organic phase change material change into a solid state to obtain phase change ceramsite.
[0065] Finally, epoxy resin, acetone and curing agent were mixed and stirred in a mass ratio of 1:0.3:0.4 to obtain epoxy emulsion. Phase change ceramsite was placed in the epoxy emulsion and stirred. After 10 seconds, it was scooped out with a colander and spread evenly until the epoxy resin hardened. An epoxy resin encapsulation layer was formed on the surface of the porous ceramsite, and the cement-based phase change aggregate was prepared.
[0066] Example 3
[0067] A method for preparing a cement-based phase change aggregate, comprising:
[0068] The porous ceramsite with a particle size of 5mm-10mm and good gradation is used as the porous aggregate for preparing phase change aggregate. Its porosity is 70%, water absorption rate is 48%, impurity content is 1.1%, and there is no debris or clay block. The appearance is oval; the inorganic phase change material selected is Na 2 SO 4 10H 2 O, its phase change temperature is 32.4℃; the organic phase change material selected is C 25 H 32 , and its phase transition temperature is 35℃.
[0069] Na 2 SO 4 10H 2 O and C 25 H 32 Put it in a temperature regulating box at 45℃ and 55℃ and keep it warm for 2 hours to turn it into liquid state.
[0070] Then put 500g of porous ceramsite into Na 2 SO 4 10H 2 O in a temperature regulating box for adsorption, adjusting the ceramsite every 3 hours until all 6 sides are adsorbed, and obtaining ceramsite adsorbed with inorganic phase change material;
[0071] Place the ceramsite adsorbed with inorganic phase change material into C 25 H 32The ceramsite was placed in a temperature regulating box and the ceramsite was adjusted every 2.5 hours until all 6 sides were adsorbed. After the adsorption was completed, the ceramsite was placed in a temperature regulating box at 15°C for 30 minutes to make the adsorbed organic phase change material change into a solid state to obtain phase change ceramsite.
[0072] Finally, epoxy resin, acetone and curing agent were mixed and stirred in a mass ratio of 1:0.2:0.1 to obtain epoxy emulsion. Phase change ceramsite was placed in the epoxy emulsion and stirred. After 10 seconds, it was scooped out with a colander and spread evenly until the epoxy resin hardened. An epoxy resin encapsulation layer was formed on the surface of the porous ceramsite, and the cement-based phase change aggregate was prepared.
[0073] Example 4
[0074] A method for preparing a cement-based phase change aggregate, comprising:
[0075] The porous ceramsite with a particle size of 5mm-10mm and good gradation is used as the porous aggregate for preparing phase change aggregate. Its porosity is 80%, water absorption rate is 51%, impurity content is 2.3%, and there is no debris or clay block. The appearance is oval; the inorganic phase change material selected is Na 2 S 2 O 3 ·5H 2 O, its phase change temperature is 48.5℃; the organic phase change material selected is C 22 H 44 O 2 , and its phase transition temperature is 80℃.
[0076] Na 2 S 2 O 3 ·5H 2 O and C 22 H 44 O 2 Put it in a temperature regulating box at 60℃ and 90℃ and keep it warm for 2 hours to turn it into liquid state.
[0077] Then put 500g of porous ceramsite into Na 2 S 2 O 3 ·5H 2 O in a temperature regulating box for adsorption, adjusting the ceramsite every 3.5 hours until all 6 sides are adsorbed, and obtaining ceramsite adsorbed with inorganic phase change material;
[0078] Place the ceramsite adsorbed with inorganic phase change material into C 22 H 44 O 2The ceramsite is placed in a temperature regulating box, and the ceramsite is adjusted every 3.5 hours until all 6 sides are adsorbed. After the adsorption is completed, the ceramsite is placed in a temperature regulating box at 15°C for 30 minutes to make the adsorbed organic phase change material change into a solid state to obtain a phase change ceramsite;
[0079] Finally, epoxy resin, acetone and curing agent were mixed and stirred in a mass ratio of 1:0.1:0.4 to obtain epoxy emulsion. Phase change ceramsite was placed in the epoxy emulsion and stirred. After 10 seconds, it was scooped out with a colander and spread evenly until the epoxy resin hardened. An epoxy resin encapsulation layer was formed on the surface of the porous ceramsite, and the cement-based phase change aggregate was prepared.
[0080] Example 5
[0081] A method for preparing a cement-based phase change aggregate, comprising:
[0082] The porous ceramsite with a particle size of 5mm-10mm and good gradation is used as the porous aggregate for preparing the phase change aggregate. Its porosity is 65%, water absorption rate is 45%, impurity content is 2.0%, and there is no debris or clay block. The appearance is oval; the inorganic phase change material selected is CaCl 2 6H 2 O, its phase change temperature is 29.7; the organic phase change material selected is C 10 H 20 O 2 , and its phase transition temperature is 32℃.
[0083] CaCl 2 6H 2 O and C 10 H 20 O 2 Put it in a temperature regulating box at 40℃ and 55℃ and keep it warm for 2 hours to turn it into liquid state.
[0084] Then put 500g of porous ceramsite into CaCl 2 6H 2 O in a temperature regulating box for adsorption, adjusting the ceramsite every 3.5 hours until all 6 sides are adsorbed, and obtaining ceramsite adsorbed with inorganic phase change material;
[0085] Place the ceramsite adsorbed with inorganic phase change material into C 10 H 20 O 2 The ceramsite is placed in a temperature regulating box, and the ceramsite is adjusted every 3.5 hours until all 6 sides are adsorbed. After the adsorption is completed, the ceramsite is placed in a temperature regulating box at 15°C for 30 minutes to make the adsorbed organic phase change material change into a solid state to obtain a phase change ceramsite;
[0086] Finally, epoxy resin, acetone and curing agent were mixed and stirred in a mass ratio of 1:0.3:0.2 to obtain epoxy emulsion. Phase change ceramsite was placed in the epoxy emulsion and stirred. After 10 seconds, it was scooped out with a colander and spread evenly until the epoxy resin hardened. An epoxy resin encapsulation layer was formed on the surface of the porous ceramsite, and the cement-based phase change aggregate was prepared.
[0087] Comparative Example 1
[0088] The porous ceramsite with a particle size of 5mm-10mm and good gradation is used as the porous aggregate for preparing the phase change aggregate. Its porosity is 60%, water absorption rate is 45%, impurity content is 1.6%, and there is no debris or clay block. The appearance is oval; the inorganic phase change material selected is CaCl 2 6H 2 O, its phase change temperature is 29.7℃; the organic phase change material selected is C 25 H 32 , and its phase transition temperature is 35℃.
[0089] CaCl 2 6H 2 O and C 25 H 32 Put it in a temperature regulating box at 45℃ or 50℃ and keep it warm for 2 hours to turn it into liquid state.
[0090] Then put 500g of porous ceramsite into CaCl 2 6H 2 O in a temperature regulating box for adsorption, and the adsorption surface is replaced every 3 hours until all 6 surfaces are adsorbed, thereby obtaining ceramsite adsorbed with inorganic phase change material;
[0091] Place the ceramsite adsorbed with inorganic phase change material into C 25 H 32 The adsorption surface was changed every 3 hours until all 6 surfaces were adsorbed. After the adsorption was completed, the ceramsite was placed in a temperature regulating box at 15°C for 30 minutes to make the adsorbed organic phase change material change into a solid state to obtain phase change ceramsite.
[0092] Adsorption test of ceramsite:
[0093] Based on Example 1, the adsorption of ceramsite to phase change material was tested, and the adsorption of ceramsite to CaCl was calculated by measuring the weight change of ceramsite before and after adsorption. 2 6H 2 O and C 25 H 32 The adsorption rate is 53.3%, which has a good adsorption effect.
[0094] Phase change aggregate permeability test:
[0095] Weigh 30g of the phase change aggregate prepared in Comparative Example 1 and Example 1 respectively, place them on filter paper, place them in an oven and heat them for 3h at 60°C, and observe the seepage of the phase change material on the filter paper. Figure 1 and Figure 2 As shown, it can be seen that the permeability of the phase change material is significantly reduced after secondary encapsulation with resin in this application.
[0096] Testing and characterization of the performance of concrete mixed with phase change aggregate (hereinafter referred to as phase change concrete):
[0097] (1) Working performance of phase change concrete
[0098] The phase change aggregate of Example 1 is used to replace the stone in an equal volume and mixed into the concrete to ensure that the phase change aggregate accounts for 5% of the cement mass. The slump and air content of the phase change aggregate concrete are tested according to the "Test Method for Performance of Ordinary Concrete Mixtures" (GB / T50080-2016) using a mix ratio of C40 strength grade, and the slump is controlled at 160mm±20mm by adjusting the water reducing agent, as shown in Table 1.
[0099] Table 1 Concrete mix proportion and properties
[0100]
[0101] Note: 1# is the reference group, 2# is the doped phase change material group.
[0102] It can be seen from Table 1 that the water reducing agent dosage and air content of the benchmark group and the doped phase change ceramsite group are basically the same, indicating that the phase change material prepared in this application will not affect the working performance of concrete.
[0103] (2) Adiabatic temperature rise of phase change concrete
[0104] The adiabatic temperature rise of phase change concrete was measured, and the results are as follows: Figure 3 , Figure 3 The influence of phase change aggregate on the adiabatic temperature rise of concrete is shown. When the total content of phase change aggregate is 5% of the cement mass, the maximum temperature rise of phase change concrete is 48.5℃, which is 8.7℃ lower than that of the benchmark group (maximum temperature rise of 57.2℃).
[0105] (3) Compressive strength of phase change concrete
[0106] In order to simulate the actual internal conditions of large-volume concrete, the concrete was placed in an insulated box for curing for 3 days and then subjected to standard curing. Figure 4 Then the compressive strength of the concrete is tested at regular intervals, and the results are shown in Figure 5 As shown. Figure 5It can be seen that the phase change aggregate of the present application will reduce the early compressive strength of concrete to a certain extent, but has little effect on the mid-to-late compressive strength of concrete.
[0107] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a cement-based phase change aggregate, characterized in that: include: Immersing the ceramsite in a liquid inorganic phase change material for adsorption to obtain ceramsite adsorbed with the inorganic phase change material; Immersing the ceramsite adsorbed with the inorganic phase change material into a liquid organic phase change material for adsorption to obtain phase change ceramsite; Epoxy emulsion is coated on the surface of the phase-change ceramsite, and after the epoxy emulsion is cured, a cement-based phase-change aggregate is obtained. The components of the epoxy emulsion include epoxy resin, diluent and curing agent.
2. The method for preparing cement-based phase change aggregate according to claim 1, characterized in that: The inorganic phase change material includes at least one of CaCl2·6H2O, Na2HPO4·12H2O, Na2S2O3·5H2O and Na2SO4·10H2O.
3. The method for preparing cement-based phase change aggregate according to claim 1, characterized in that: The organic phase change material comprises C 25 H 32 , C 18 H 38 , C 22 H 44 O2、C 12 H 26 O.C 16 H 32 O2、C 10 H 20 O2 and C 12 H 24 At least one of O2.
4. The method for preparing cement-based phase change aggregate according to claim 1, characterized in that: The particle size of the ceramsite is 5mm-10mm.
5. The method for preparing cement-based phase change aggregate according to claim 1, characterized in that: The porosity of the ceramsite is 50-80%.
6. The method for preparing cement-based phase change aggregate according to claim 1, characterized in that: In the epoxy emulsion, the mass ratio of the epoxy resin, the diluent and the curing agent is 1:(0.1-0.3):(0.1-0.5).
7. The method for preparing cement-based phase change aggregate according to claim 1, characterized in that: The method of immersing ceramsite in a liquid inorganic phase change material for adsorption comprises: heating the inorganic phase change material to above its phase change temperature; The ceramsite is completely immersed in the inorganic phase change material, and the surface of the ceramsite in contact with the bottom of the container is adjusted every 2.5-4 hours until all six surfaces of the ceramsite are in contact with the bottom of the container once.
8. The method for preparing cement-based phase change aggregate according to claim 1, characterized in that: The diluent includes at least one of acetone, toluene, xylene, styrene, ethyl acetate and butyl acetate.
9. The method for preparing cement-based phase change aggregate according to claim 1, characterized in that: The curing agent is an amine curing agent.
10. A cement-based phase change aggregate, characterized in that: The phase change aggregate is prepared by the preparation method described in any one of claims 1-9.